2015
DOI: 10.1080/00222895.2014.983450
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Acute Aerobic Exercise on the Primary Motor Cortex

Abstract: The effect of aerobic exercise on primary motor cortical excitability is a relevant area of interest for both motor learning and motor rehabilitation. Transient excitability changes that may follow an exercise session are a necessary precursor to more lasting neuroplastic changes. While the number of studies is limited, research suggests that a session of aerobic exercise can create an ideal environment for the early induction of plasticity. Potential mechanisms include the upregulation of neurotransmitter act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 130 publications
2
65
0
2
Order By: Relevance
“…31,32 Moreover, previous studies performed in human and animal models have demonstrated the role of physical exercises as a stimulating factor of neural plasticity by the increase of brain-derived neurotrophic factor (BDNF) levels, axonal regeneration, and the promotion of long-term potentiation (LTP)-like plasticity in the motor cortex. [33][34][35][36] Also, physical exercise has been proven to provide beneficial effects in the cerebellar mitochondrial bioenergetics systems of rats, 37 and this could be used as a model for a therapeutic approach for SCA2 patients in which the bioenergetic deficits caused by the ataxin-2 mutation 38-40 could be alleviated.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Moreover, previous studies performed in human and animal models have demonstrated the role of physical exercises as a stimulating factor of neural plasticity by the increase of brain-derived neurotrophic factor (BDNF) levels, axonal regeneration, and the promotion of long-term potentiation (LTP)-like plasticity in the motor cortex. [33][34][35][36] Also, physical exercise has been proven to provide beneficial effects in the cerebellar mitochondrial bioenergetics systems of rats, 37 and this could be used as a model for a therapeutic approach for SCA2 patients in which the bioenergetic deficits caused by the ataxin-2 mutation 38-40 could be alleviated.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown the benefits of physical exercise on academic achievement, mental health, and cognition, mostly in study populations of adolescents and young school children (Tomporowski et al, 2008). The impact of exercise has been shown to be beneficial in relation to several health outcomes (Knapen, Vancampfort, Moriën, & Marchal, 2015;Sanchis-Gomar et al, 2015;Singh & Staines, 2015). Recent research has reported that exercise can improve mental health, being recognized as a major stress reliever and a form of treating depression (Knapen et al, 2015).…”
Section: Evidence From Concurrent Findingsmentioning
confidence: 99%
“…This could explain why the high-intensity exercise used in our study may be effective in inducing motor cortical excitability changes. A neurochemical model has also been proposed to explain the effects of exercise on motor cortical excitability through modulation of arousal-related neurotransmitters, including dopamine, serotonin, and norepinephrine 39 . Brain-derived neurotrophic factor (BDNF) is also a potential candidate for increasing motor cortical excitability after exercise.…”
Section: Discussionmentioning
confidence: 99%